Mechanistic basis for Cancer Immune Evasion and role of immune checkpoint blockades in Immuno-Oncology - Benjamin A Babalola; Gboyega E Adebami; Samuel E Akinsuyi (Global Journal of Cancer Therapy - Peertechz Publications, 2021)
Cancer biology clinical breakthroughs in this millennium requires the development of new methods and techniques to suit the challenge of the global health menace. Immunotherapy is a technique that has engendered advancement in cancer studies. Immuno-oncology aims at the recognition of tumour antigens and elimination of tumour cells. In this paper, the pathogenesis of carcinogenesis and role of immunosurveillance in tumour prevention is critically analyzed. The paper also attempts to show the role of MHC-I and IFN signaling, the concerted effort of Cytotoxic T-Lymphocyte-Associated Protein 4 (CTLA-4), Programmed Cell Death Protein 1 (PD-1) and Programmed Death-Ligand 1 (PD-L1), and metabolic alteration in immune evasion mechanism of cancerous cells. The use of Immune Checkpoint Inhibitors (ICPIs) in combination with anti-CTLA-4 and anti-PD-1 antibodies has increased survival in some cancers and shows promise in others. When these agents are administered, however, there are toxicities known as "Immune-related adverse events." A brief overview on the dermatologic toxicity, endocrinopathy, hepatotoxicity and diarrhoea/enterocolitis is discussed. This paper concludes by mentioning the promising potential of genomic sequencing technology in cancer immunotherapy.